2023
DOI: 10.1108/tr-04-2022-0190
|View full text |Cite
|
Sign up to set email alerts
|

Destination image: a consumer-based, big data-enabled approach

Abstract: Purpose This study aims to use a bottom-up, inductive approach to derive destination image attributes from large quantities of online consumer narratives and establish a destination classification system based on relationships among attributes and places. Design/methodology/approach Content and social network analyses were used to explore the consumer image structure for destinations based on online narratives. Cluster analysis was then used to group destinations by attributes, and ANOVA provided comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…One of these accepted and widely used segmentation methods in marketing literature is K-means (Zhong et al , 2023). Segmentation with the K-means method gives researchers the freedom to choose an appropriate number of segments according to the interpretability of results and managerial purposes (Park and Yoon, 2009).…”
Section: Materials and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…One of these accepted and widely used segmentation methods in marketing literature is K-means (Zhong et al , 2023). Segmentation with the K-means method gives researchers the freedom to choose an appropriate number of segments according to the interpretability of results and managerial purposes (Park and Yoon, 2009).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…After clustering, the accuracy of this step was measured by statistical tests. Following Zhong et al (2023), we performed the analysis of variance test separately on all features. The results of this test showed that for all properties, the p -value is less than 0.001, and that there is a significant difference between the different partitions, so it can be concluded that the partitions are different.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…These provide the opportunity to process, store and access knowledge while being connected through mobile devices (Iranmanesh et al, 2022). Technological breakthroughs like Artificial Intelligence (AI), robotics, the Internet of Things (IoT), autonomous vehicles, Blockchain, Big Data, cloud computing, speech, facial recognition (Jabeen et al, 2022;Li et al, 2021;G€ ossling, 2020;Filimonau and Naumova, 2020;Huang and Rust, 2021;€ Onder and Gunter, 2020;Zaman et al, 2022), social media, intelligent service desks, Metaverse (Buhalis et al, 2023b), Virtual Reality (VR) and Augmented Reality (AR) (Cranmer et al, 2021), multiply these opportunities for both consumers and businesses (Zhong et al, 2023;Chen et al, 2022). Some technologies have disrupted and transformed the operation of tourism and hospitality businesses by changing entire business models (Abou Kamar et al, 2024;Fennell, 2021).…”
Section: Transformative Changesmentioning
confidence: 99%
“…Technological breakthroughs like Artificial Intelligence (AI), robotics, the Internet of Things (IoT), autonomous vehicles, Blockchain, Big Data, cloud computing, speech, facial recognition (Jabeen et al ., 2022; Li et al ., 2021; Gössling, 2020; Filimonau and Naumova, 2020; Huang and Rust, 2021; Önder and Gunter, 2020; Zaman et al ., 2022), social media, intelligent service desks, Metaverse (Buhalis et al. , 2023b), Virtual Reality (VR) and Augmented Reality (AR) (Cranmer et al ., 2021), multiply these opportunities for both consumers and businesses (Zhong et al ., 2023; Chen et al ., 2022).…”
Section: The Evolution Of Technologies In Tourism and Hospitalitymentioning
confidence: 99%